An analysis of 1999 world health organisation (WHO) guidelines for drug donations for better donation practice in emergency situations - Joep Ahmed Djojodibroto; Reinhard Huss (Journal of Health Technology Assessment in Midwifery, 2018)
In disasters and emergency situations, a lot of drug and medical supplies comes to the affected area from local or international donors. But, those donations often generate more problems for the recipients. The WHO and major humanitarian organisations developed WHO Guidelines for Drug Donations in 1996. The guidelines based on four core principles which are all donation should benefit the recipient, respect for wishes and authority of the recipient, there should not be a double standard in quality, and effective communication between donor and recipient. The guidelines influenced positively to drug donation practices for several years until 2004. The drug donation practices during 2004 tsunami relief in Sri Lanka and Aceh (Indonesia) showed that the compliance with WHO Guidelines for Drug Donations was low. This study aim was to strengthen the effectiveness of WHO Guidelines for Drug Donations in disaster and emergency situations. While the objectives are to explore the strength and weakness of the WHO Guidelines for Drug Donations and to recommend how to improve the effectiveness of drug donations. In this study, the WHO Guidelines for Drug Donations were analysed using the model of health policy analysis from Walt and Gilson, which is specifically used for analysing health policies. The framework is viewed as a tool to describe the interactions and interconnections systems between content, context, process and groups of actors. The author concludes that presence of donation operator team for drug donations is needed during the emergency situations and it should be stated in the WHO Guidelines for Drug Donations. The WHO needs to encourage donors and recipients to refer to WHO Guidelines for Drug Donations when they are making their own guidelines. The guidelines can be strengthened at country level and adjusted to regulations in the countries. The WHO Guidelines for Drug Donations should state that donations are preferred in form of New Emergency Health Kit (NEHK) or cash donations, and the necessity of information and communication centre in the WHO Guidelines for Drug Donations.